NANOTECHNOLOGY AS A PART OF PHYSICS TEACHING AT SCHOOL - Budzik, Sylwia; Kizowski, Czesław (Concepts of Physics, 2008)
The progress in teaching should be in accord with the progress of science, that’s why the subject of teaching must be supplemented by the elements of modern knowledge which permit pupils to understand better what happens around us. The end of XX century is characterised by the rapid development of nanotechnology, which we deal with in this paper.